Pregnant and postpartum women perceptions about waitingroom in a Primary Health Care Unit included in the Family Health Strategy - Juliana Ebling Brondani; Ana Laura Aranda; Vanessa Lago Morin; Thaíse da Rocha Ferraz; Clara Leonida Marques Colomé; Elenir Fedosse (Universidade de Fortaleza, 2013)
Objective: To analyze the perception of pregnant and postpartum women about their experiences in the waiting room. Methods: A descriptive analytic study, of qualitative approach, conducted in a Primary Health Care Unit integrated into the Family Health Strategy (Estratégia Saúde da Família-PSF) in a municipality of the state of Rio Grande do Sul, Brazil. The data was collected in December 2011, through interviews with open and closed questions, and was analyzed using content analysis technique. The sample consisted of 10 women, seven of them being pregnant and three in postpartum period; all having received prenatal care and taken part in waiting room activities from September to December 2011. Results: According to the participants' perception, the waiting room is a space of attentiveness, promoter of tranquility, understanding and clarification of questions related to pregnancy and childbirth process. Conclusions: The formation of health education groups intermediated by problem-based dialogue, aiming to promote reciprocal learning and teaching, with focus on the extensive concept of health, is a relevant issue in the waiting room. It is also important to highlight the need to accomplish continuing education initiatives involving healthcare professionals, centered on a questioning approach of social reality and services, along with the integration of managerial, educational and political aspects. This shall contribute to the real construction of politicized knowledge in health, as report the official documents of health and education sphere.